Efeitos do treinamento muscular ventilatório sobre a hemodinâmica, variabilidade da frequência cardíaca e músculos periféricos e diafragma em ratos com diabetes mellitus - Costa, Cínthia de Sousa (Universidade Federal de São Carlos, 2020)
Introduction: Diabetes mellitus (DM) is one of the main chronic diseases that affects the population, being considered a serious public health problem. Ventilatory muscle training (VMT) has been shown to improve clinical outcomes in DM patients, however, little is known about its effect on some pathophysiological mechanisms of DM. Still, no study has verified the hemodynamic mechanisms, heart rate control and muscle variability promoted by VMT in DM. Objectives: To verify the effects of VMT on hemodynamics, heart rate variability (HRV) DM rats induced by streptozotocin infusion (STZ). Study Design: Animal experimental study. Methods: Thirty-six male Wistar rats were randomized into 4 groups: sham group - sedentary (Sham-ST; n = 9); sham group with VMT (Sham- VMT; n = 9); DM group - sedentary (DM-ST; n = 8) and DM group with VMT (DM- VMT; n = 8). Hemodynamics were assessed by central cannulation and HRV was calculated by ECG. In addition, muscle cross-sectional area of diaphragm, anterior tibial and soleus were verified. Results: Induction of DM by STZ resulted in weight loss, hyperglycemia, reduced blood pressure, increased HR and slower left ventricular contraction and relaxation (P <0.05). We also observed a decrease in the RMSSD index, and in the cross-sectional area of the muscles, they showed a smaller area of muscle fibers in the diaphragm, soleus and anterior tibial muscles in diabetic rats (P <0.05). Interestingly, however, TMV led to an attenuation of HR in healthy animals and an increase in RMSSD in diabetic rats (P <0.05). Conclusion: The induction of DM produces profound deleterious changes in the diaphragmatic and peripheral muscles, with impairments in cardiovascular hemodynamics and in autonomic control. However, TMV can beneficially attenuate autonomic changes, with an improvement in parasympathetic modulation.
Effects of ventilatory muscle training on hemodynamics, heart rate and peripheral muscle variability and diaphragm in rats with diabetes mellitus
Keywords: Diabetes mellitus; Treinamento muscular ventilatório; Controle autonômico; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL